The Bulacan Provincial Library and its community an information needs analysis - Avila, Lenra Machrine E. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The study aimed to identify the information needs of the residents of Malolos City to assess how the Bulacan Provincial Library meets information needs of its residents. The study also aimed to identify the gaps between, public library standards of the Board for Librarians (BFL), current library collections and services, perceptions of the residents and expectations of the library staff with reference to meeting the stated goals and objectives of the Bulacan Provincial Library.